The Creative Gesture - Bellini, Pier Paolo (Springer Nature Switzerland, 2024)
1. Nature and Sources of Creativity – 2. Creativity and contexts – 3. The “creative processes” – 4. Relational Dimension of Creativity. This open access book offers a concise overview of the theories constructed within the various human sciences around the theme of creativity as a symbolic capacity to link things together: it manifests itself when the individual endowed with a certain type of intelligence encounters cultural and social conditions that enable them to develop that capacity to the maximum, rather than inhibiting it or diverting it to other fields where it is doomed to failure. Even the most intimate of human expressiveness is considered as a result of an active social relationality. Social dimensions of creativity (evaluation, primary socialization, motivation, leadership) and “creative processes” (creative attitude, creative gesture, divergent thinking, problem-solving capacity, interdisciplinary approach, randomness, algorithmic creativity) are also analysed. The book concludes by evaluating the course taken in the light of the relational theory of society: the development of creativity cannot be conceived outside of self-other relations. This book is the result of a translation done with the help of artificial intelligence. The text has subsequently been revised further by a professional copy editor in order to refine the work stylistically. Pier Paolo Bellini is Associate Professor at University of Molise, Italy. His research focuses on the sociology of cultural and communicative processes, with a special interest in the characteristics of artistic communication and its intercultural potential. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
10.1007/978-3-031-54219-0
Keywords: Creative writing.; Psychology.; Aesthetics.; Culture.; Knowledge; Sociology of.